2003
DOI: 10.1590/s1413-70542003000500027
|View full text |Cite
|
Sign up to set email alerts
|

Efeito das formas de apresentação do milho e do uso de pedrisco na ração, sobre o desempenho de frango de corte

Abstract: RESUMO Para avaliar a influência das formas de apresentação do milho e a presença de pedrisco granítico sobre o desempenho em frangos de corte, utilizaram-se 720 frangos com 22 dias de idade, de ambos os sexos, submetidos aos tratamentos: forma de apresentação do milho (inteiro, moído grosso e moído fino), pedrisco (ausên-cia e presença) e sexo (macho e fêmea). O experimento foi conduzido em um delineamento inteiramente casualizado (DIC) em esquema fatorial 3 x 2 x 2 (formas de apresentação do milho, sem e com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…Some researchers [1,2,11] stated that there were no differences with using grit among the groups in terms of carcass yield and relative percentages of organ weight. Some early studies [1,[26][27][28] showed that granite grit usage increased the weight of gizzard but had no effect on performance of broilers, which is also consistent with our results. This result can be explained by a large proportion and different size of the grit stones consumed by chicks retained in the gizzard [2,29] .…”
Section: Discussionsupporting
confidence: 93%
“…Some researchers [1,2,11] stated that there were no differences with using grit among the groups in terms of carcass yield and relative percentages of organ weight. Some early studies [1,[26][27][28] showed that granite grit usage increased the weight of gizzard but had no effect on performance of broilers, which is also consistent with our results. This result can be explained by a large proportion and different size of the grit stones consumed by chicks retained in the gizzard [2,29] .…”
Section: Discussionsupporting
confidence: 93%